2022
DOI: 10.3390/gels8040243
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Cattle Slaughtering Industry By-Products: Modification of the Functional Properties and Structural Characteristics of Cowhide Gelatin Induced by High Hydrostatic Pressure

Abstract: This study investigates the effects of different pressures (200, 250, 300, 350, and 400 MPa) and durations (5, 10, 15, 20, and 25 min) on the functional properties, secondary structure, and intermolecular forces of cowhide gelatin. Our results show that high hydrostatic pressure significantly affected the two, three, and four-level structures of gelatin and caused the contents of the α-helix and β-turn to decrease by 68.86% and 78.58%, respectively (p < 0.05). In particular, the gelatin at 300 MPa for 15 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…These results suggested that the protein aggregation induced by HPH overtreatment might be due to the rearrangement of the disordered structure and the increase in the ordered structure of the protein, resulting in a decrease in protein solubility. Gao et al [ 67 ] found the solubility of cowhide gelatin induced by high hydrostatic pressure first increased and then decreased with the increase in pressure (200–400 MPa); at the same time, the α-helix structure first decreased and then increased. The opposite was true for the random coil structure, which converts, causing the structure of the gel to be more compact and orderly.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the protein aggregation induced by HPH overtreatment might be due to the rearrangement of the disordered structure and the increase in the ordered structure of the protein, resulting in a decrease in protein solubility. Gao et al [ 67 ] found the solubility of cowhide gelatin induced by high hydrostatic pressure first increased and then decreased with the increase in pressure (200–400 MPa); at the same time, the α-helix structure first decreased and then increased. The opposite was true for the random coil structure, which converts, causing the structure of the gel to be more compact and orderly.…”
Section: Resultsmentioning
confidence: 99%